Correlation between Plasma Osteopontin and Alkaline Phosphatase in Type 2 Diabetes Mellitus Patients - Sinambela, Josua TH; Pramudianti, M.I Diah; Ariningrum, Dian (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Diabetes Mellitus (DM) is a chronic disease caused by pancreas the inability to produce insulin or ineffectively insulin use.Fracture risk in type 2 DM patients increases even though the bone density is normal. This study aimed to examine thecorrelation of osteopontin (OPN) and alkaline phosphatase (ALP) in type 2 DM patients. An observational analytical studywas conducted in 73 type 2 DM patients in Dr. Moewardi Hospital, Surakarta from October to November 2018. The subjectswere examined for blood pressure, fasting blood glucose, two hours postprandial blood glucose, HbA1c, OPN, and ALPlevels. P-value <0.05 was statistically significant with a 95% confidence interval. Poorly controlled type 2 DM had higher OPNlevels than well-controlled (20.5±2.8 vs. 14.8±3.1 ng/mL, p <0.001). The ALP concentration was also higher in poorlycontrolled type 2 DM patients (79.9±31.7 vs. 61.1±25 U/L, p=0.003). The levels of OPN and ALP were significantly correlatedin type 2 diabetes (r=0.273; p=0.020) and in well-controlled patients (r=0.353; p=0.047) but no correlation was found inpoorly controlled type 2 DM patients (r= -0.073; p= 0.652). In this study, a significant correlation was found between OPNand ALP in patients with type 2 DM and well-controlled. Further study involving healthy controls and bone ALPmeasurement is needed.